Analysis of Non-Performing Financing Factors and Their Resolution at the Ar-Rizqiyah Women’s Cooperative in Abar-Abir Village - Sholihah, Irmatus; Umam, M. Shaiful (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the factors contributing to non-performing financing and the resolution strategies implemented by the Ar-Rizqiyah Women’s Cooperative in Abar-Abir Village. The research employs a descriptive qualitative approach using field research methods. Data were obtained through direct observation, in-depth interviews with cooperative managers and members, and documentation. The results show that non-performing financing is caused by two main factors: internal factors such as weak feasibility analysis, limited managerial competence, and poor monitoring systems; and external factors such as borrowers' low commitment to repayment, misuse of funds, and business losses. Resolution strategies include preventive measures based on the 5C principles (Character, Capacity, Capital, Collateral, and Condition of Economy), as well as Sharia-based dispute resolution methods, including peaceful negotiation (al-Sulh), arbitration (at-Tahkim), and litigation (al-Qadha). In conclusion, the application of the 5C principles and Sharia-compliant dispute resolution approaches is effective in reducing non-performing financing and strengthening the cooperative's financial sustainability.